Base pressure control and temperature distribution along the duct at supersonic Mach number: a comprehensive CFD approach - part II - Jais, Amirullah; Khan, Ambareen; Akhtar, Mohammad Nishat; Khan, Sher Afghan (Pushpa Publishing House, 2025)
The development of space shuttles and high-performance military aircraft has made the study of turbulent flow in separated regions a key area of research. Researchers are also interested in turbulent flow under transonic and supersonic conditions, particularly when it separates suddenly and expands after the cross-section of the larger duct increases rapidly. Two regions where the shear layer forms are the separated flow and the main flow. The split streamline reattaching to the duct causes significant drag and creates a recirculation zone where the pressure is lower than in the surrounding air. This study investigates the use of quarter-circular ribs to regulate base pressure as a passive control method, where the shear layer hits the straight part of the rib and the curved part is downstream. Computational simulations investigate how the rib radius and placement near a backward-facing step influence flow behavior, including recirculation and vortex formation. In the study, the inertia parameters considered were a Mach number of M = 1.7 and the nozzle pressure ratio (NPR) in the range of 3 to 11. The geometrical parameters considered were the area ratio A2/A1 = 4, the cross-sectional area of the duct-to-nozzle exit, and the length-to-diameter L/D ratio, ranging from 1 to 6. The quarter-circle radius considered was 1.5 mm, 2 mm, and 3 mm, and the ribs were located at L/D = 0.5, 1, 1.5, and 2. The goal is to identify the optimal rib geometry and location that maximizes aerodynamic efficiency. The results show the optimum rib radius and locations. Base Pressure Control and Temperature Distribution are 3 mm and L/D = 2. The rib radius of 1.5 mm does not show any definite pattern. In contrast, the 3 mm rib radius exhibits a progressive increase in the base at various locations within the duct. Hence, a 3 mm rib radius seems to be the best option if the application is to reduce the base drag to a considerable level